Kajian Perubahan Sistem Pembayaran Pajak Online Terhadap Wajib Pajak : (Studi Kasus di Restoran CV. X Kota Surabaya) - Risda Vera Fitria; Heri Toni Hendro P; Diana Zuhroh; Tjandra Wasesa; Wiratna Wiratna (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This research is about the analysis of changes in the online tax payment system for CV restaurant taxpayers. X City of Surabaya. It aims to find out the negative and positive impacts for taxpayers by using the theory of online tax payment in the characteristics of tax surveillance applications to the advantages and disadvantages. This study uses a qualitative research method with the results of the study showing that changes in the payment system using the tax surveillance application still experience technological obstacles that result in inefficiencies in the implementation of online restaurant tax payments.